Hi Teresa,
Always remember:
ln x = loge(log base e)x
log x = log10(log base 10)x
Example : ln x = 2
loge x = 2
x = e^2
log x = 5
log10 x =5
x = 10^5
(Hope this two examples have given you a rough understanding)
ln(x-4) = -3
ln(x-4) = loge(x-4),right?
loge(x-4) = -3
We need to get rid off the ln sign,how to do this?(refer to the examples above)
Shift the exponential sign to the right hand side, so the right hand side becomes e^-3
Now,x-4 = e^-3
x = 4+e^-3 (compute the answer)
Thats all! Easy right ? :)
Do more practices. Good luck! :)
how to solve this problem ln(x-4)=-3
1 answer